2004
DOI: 10.1097/00004647-200404000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Glucose Influx and Blood Flow in Retina and Brain of Diabetic Rats

Abstract: Summary:Diabetes is associated with extensive microvascular pathology and decreased expression of the glucose transporter (GLUT-1) in retina, but not brain. To explore the basis of these differences, the authors simultaneously measured glucose influx (mol · g −1 · min) and blood flow (mL · g −1 · min −1 ) in retina and brain cortex of nondiabetic control rats (normoglycemic and acute-hyperglycemic) and in rats with streptozotocin-induced diabetes (with or without aminoguanidine (AMG) treatment) using a single-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 38 publications
(58 reference statements)
5
34
0
Order By: Relevance
“…The D-glucose K m at the BBB is between 2 and 11 mmol/L (Puchowicz et al, 2004), which agrees with our finding. However, a previous in situ mouse brain perfusion study found a higher K m (B17 mmol/L) (Dagenais et al, 2000).…”
Section: Controlsupporting
confidence: 93%
See 1 more Smart Citation
“…The D-glucose K m at the BBB is between 2 and 11 mmol/L (Puchowicz et al, 2004), which agrees with our finding. However, a previous in situ mouse brain perfusion study found a higher K m (B17 mmol/L) (Dagenais et al, 2000).…”
Section: Controlsupporting
confidence: 93%
“…Some studies suggest that the eye V max is higher than that for the brain because there is more GLUT1 in the rat retinal capillaries than in the rat brain capillaries (Badr et al, 2000). An in vivo rat study that measured glucose influx into both the brain and retina using a blood glucose concentration of 2 to 32 mmol/L, confirms that the glucose influx obeys MichaelisMenten kinetics at the brain but not at the retina (Puchowicz et al, 2004). This observation for the retina agrees with our finding, because the glucose influx rate is proportional and linear when the glucose concentration is below or close to the K m value.…”
Section: Controlmentioning
confidence: 96%
“…The backflux error is proportional to CBF and the duration of the experiment and is inversely proportional to the brainblood partition coefficient for the indicator. (Harik et al, 1994;Puchowicz et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Three samples (5 mL each) of the prevalently venous blood that dripped from the foramen magnum were collected to estimate radioactivity (liquid b-scintillator, LS 6500, Beckman, Fullerton, CA, USA) in the cerebral intravascular space (Harik et al, 1994;Puchowicz et al, 2004). Aliquots of the withdrawn arterial blood were taken for radioactivity measurement.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, D-mannitol, a representative nonpermeable paracellular marker, exhibits very low blood-to-retina influx permeability while D-glucose and amino acids, the substrates of membrane transporter molecules, exhibit over a 300-fold higher permeability than that of D-mannitol (Puchowicz et al, 2004;). These pieces of evidence strongly suggest that the inner BRB is a selective barrier for the retina.…”
Section: Molecular Aspects Of the Barrier Structurementioning
confidence: 99%